MASP-1 Increases Endothelial Permeability - Debreczeni, Márta L.; Németh, Zsuzsanna; Kajdácsi, Erika; Schwaner, Endre; Makó, Veronika; Masszi, András; Doleschall, Zoltán; Rigó, János; Walter, Fruzsina R.; Deli, Mária A.; Pál, Gábor; Dobó, József; et al. (Frontiers in Immunology, 2019)
Pathologically increased vascular permeability is an important dysfunction in the pathomechanism of life-threatening conditions, such as sepsis, ischemia/reperfusion or hereditary angioedema (HAE), diseases accompanied by uncontrolled activation of the complement system. HAE for example is caused by the deficiency of C1-inhibitor (the main regulator of early complement activation), which leads to edematous attacks threatening with circulatory collapse. We have previously reported that endothelial cells become activated during HAE attacks. A natural target of C1-inhibitor is mannan-binding lectin-associated serine protease-1 (MASP-1), a multifunctional serine protease, which plays a key role in the activation of complement lectin pathway. We have previously shown that MASP-1 induces the proinflammatory activation of endothelial cells and in this study we investigated whether MASP-1 can directly affect endothelial permeability. All experiments were performed on human umbilical vein endothelial cells (HUVECs). Real-time microelectric sensing revealed that MASP-1 decreases the impedance of HUVEC monolayers and in a recently developed permeability test (XperT), MASP-1 dose-dependently increased endothelial paracellular transport. We show that protease activated receptor-1 mediated intracellular Ca2+-mobilization, Rho-kinase activation dependent myosin light chain phosphorylation, cytoskeletal actin rearrangement, and disruption of interendothelial junctions are underlying this phenomenon. Furthermore, in a whole-transcriptome microarray analysis MASP-1 significantly changed the expression of 25 permeability-related genes in HUVECs – for example it up-regulated bradykinin B2 receptor expression. According to our results, MASP-1 has potent permeability increasing effects. During infections or injuries MASP-1 may help eliminate the microbes and/or tissue debris by enhancing the extravasation of soluble and cellular components of the immune system, however, it may also play a role in the pathomechanism of diseases, where edema formation and complement lectin pathway activation are simultaneously present. Our findings also raise the possibility that MASP-1 may be a promising target of anti-edema drug development.